2000
DOI: 10.1093/sleep/23.5.1h
|View full text |Cite
|
Sign up to set email alerts
|

Slow-Release Caffeine: A New Response to the Effects of a Limited Sleep Deprivation

Abstract: . It is found in coffee, of course, but also in tea, chocolate-flavored products and cola-based beverages, etc. 1 Due to its behavioral and psychomotor stimulating properties, it is used to maintain vigilance, memory, and performance levels during limited sleep deprivation. [2][3][4][5][6][7][8] Some prolonged sleep deprivation and wake-sleep rhythm disruptions are common in everyday life, especially in emergency cases, during rescue operations, in the army, or during transmeridian flights. These situations le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 35 publications
4
29
2
Order By: Relevance
“…However, in contrast to our findings, three adverse events were reported for the SRC group, including an episode of anxiety in one subject, and one episode of trembling and diarrhea in another. The observed differences between the results of the present study, and those of Lagarde et al [20] and Petat et al [3], is likely related to the differences in the dosage used. By comparison, we used a relatively moderate dose (approx.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…However, in contrast to our findings, three adverse events were reported for the SRC group, including an episode of anxiety in one subject, and one episode of trembling and diarrhea in another. The observed differences between the results of the present study, and those of Lagarde et al [20] and Petat et al [3], is likely related to the differences in the dosage used. By comparison, we used a relatively moderate dose (approx.…”
Section: Discussioncontrasting
confidence: 94%
“…Although a number of these studies have reported SRC tolerability [21] and some have reported adverse events [21,26], studies have been limited to the acute response following a single 150-600 mg dose of SRC [3,20]. Lagarde and colleagues [20] examined a number of cardiovascular parameters including heart-rate, blood pressure and blood chemistry prior to and following the acute ingestion of 150, 300 and 600 mg of SRC in healthy male and female participants. Participants were subjected to 32-hours of sleep-deprivation in a cross-over design with a 1-week wash out period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Slow release caffeine tablets were effective for 13 h in alleviating fatigue-related decrements of vigilance and performance after limited sleep deprivation. The 300 mg dose was the most effective [77].…”
Section: Influence Of Daytime and Fatiguementioning
confidence: 93%